COD and Ammonia Characteristics of Keputih IPLT Oxidation Ditch Effluent for Integrated Treatment - Muhammad Khilmi Alkhatib; Aulia Ulfah Farahdiba (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Fecal Sludge Treatment Plants (IPLT) play an important role in treating fecal sludge before final effluent discharge or reuse. Keputih Surabaya IPLT applies an integrated treatment sequence consisting of solid-liquid separation, flow equalization, aerobic biological treatment, clarification, sludge handling, and final polishing. This study aimed to characterize Chemical Oxygen Demand (COD) and ammonia concentrations in undiluted intermediate effluent collected from the oxidation ditch outlet of Keputih Surabaya IPLT. The sample represented wastewater conditions after aerobic biological treatment, not the final effluent of the entire treatment system. COD was analyzed using the closed reflux spectrophotometric method according to SNI 6989.2:2019, while ammonia was analyzed using the phenate spectrophotometric method according to SNI 06-6989.30-2005. The results showed that COD and ammonia concentrations were 2,866.67 mg/L and 43.40 mg/L, respectively. Based on the influent flow rate of 137 m³/day, the applicable standards are 100 mg/L for COD and 10 mg/L for ammonia. Diagnostic comparison showed compliance gaps of 2,766.67 mg/L for COD and 33.40 mg/L for ammonia, with minimum removal requirements of 96.51% and 76.96%, respectively. These findings indicate that the oxidation ditch intermediate effluent still contains substantial organic and nitrogen loads. Therefore, optimization of the existing integrated treatment sequence, particularly the balancing tank, oxidation ditch, clarifier, and polishing pond, is required. Additional aerobic biofilm or moving bed biofilm reactor treatment may be considered if downstream units remain insufficient to achieve the required final effluent quality. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communiti